Gunung sebagai Tanda Kekuasaan Allah: Analisis Tafsir Ayat-ayat tentang Eksistensi Gunung - Sholihah, Putri Dewi (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2025)
This article examines the existence of mountains as a sign of Allah's power based on the interpretation of Qur'anic verses, especially QS. Fussilat verses 9-10, QS. Hud verse 43, and QS. Mountains not only act as physical elements that stabilize the earth through their sturdy roots, but also as a source of blessings, sustenance, and ecosystem balance. The research method used in this study is a qualitative method with a library research approach. This research is descriptive-analytical, which aims to explore the meaning of the Qur'anic verses about the existence of mountains and explore how classical and contemporary mufasir interpret them. Through the approach of several books of tafsir, this article explains how mountains were created with certain purposes, such as maintaining the stability of the earth, providing water sources, minerals, and habitat for flora and fauna. In addition, mountains also symbolize the firmness of faith and piety in facing the trials of life. This study emphasizes that the creation of the universe, including mountains, contains signs of Allah's greatness that encourage humans to continue to research and contemplate His power. The merging of faith and science perspectives in this article provides new insights into the harmonious relationship between religion and science in understanding the universe.